2000
DOI: 10.1128/jvi.74.4.1767-1774.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Benefits of Short-Term 9-[2-( R )-(Phosphonomethoxy)Propyl]Adenine (PMPA) Administration to Newborn Macaques following Oral Inoculation with Simian Immunodeficiency Virus with Reduced Susceptibility to PMPA

Abstract: Simian immunodeficiency virus (SIV) infection of newborn macaques is a useful animal model of humanpediatric AIDS to study pathogenesis and to develop intervention strategies aimed at preventing infection or delaying disease progression. In previous studies, we demonstrated that 9-[2-(R)-(phosphonomethoxy)propyl] adenine (PMPA; tenofovir) was highly effective in protecting newborn macaques against infection with virulent wild-type (i.e., drug-susceptible) SIVmac251. In the present study, we determined how redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 51 publications
1
40
1
3
Order By: Relevance
“…Lower acute viremias in the other four macaques may have diminished their risk of acquiring resistance. These data suggest selection of resistance during PrEP may be less frequent than during treatment of established infections (17)(18)(19). The macaque studies also provide qualitative information on how drug resistance emerges, and how reversion to wild-type may occur.…”
Section: (Materials and Methods)mentioning
confidence: 91%
See 2 more Smart Citations
“…Lower acute viremias in the other four macaques may have diminished their risk of acquiring resistance. These data suggest selection of resistance during PrEP may be less frequent than during treatment of established infections (17)(18)(19). The macaque studies also provide qualitative information on how drug resistance emerges, and how reversion to wild-type may occur.…”
Section: (Materials and Methods)mentioning
confidence: 91%
“…The macaque studies have shown that PrEP can be highly effective in preventing infection; for example, the risk of SHIV infection in macaques receiving daily PrEP with FTC or Truvada was 3.8-and 7.8-fold, respectively, lower than in untreated macaques (17). However, macaques exposed to an SIV isolate carrying the TDF resistance mutation (K65R) were not protected by TDF, which suggests PrEP may be less effective against ARV-resistant viruses (19). Substantial reductions in viremia and blunted acute viremias (up to 2log 10 reduction) have been observed in a patient failing Truvada and in macaques failing PrEP with FTC, Truvada, or a CCR5 inhibitor (17,18,(20)(21)(22).…”
Section: (Materials and Methods)mentioning
confidence: 96%
See 1 more Smart Citation
“…K65R SIV mutants also accumulate other mutations in RT, which are believed to be compensatory and improve replication fitness in vivo (80,81). These K65R SIV mutants, when inoculated in infant or juvenile macaques in the absence of tenofovir treatment, were found to replicate to high levels and be as virulent as wild-type virus with similar time to disease without reversion to the wild type (46,81,89). Persistent suppression of virulent K65R SIV mutants has only been observed in tenofovir-treated animals.…”
Section: The Cutoff Value Was 50 Sfc Per Million Cells Prior To the mentioning
confidence: 99%
“…Similarly to observations in our previous studies (60,61,69,71,72), the detection of K65R in virus isolates coincided with or was followed by the development of other mutations in RT (such as K64R, N69S, I118V, and S211N), which are thought to be compensatory mutations (as they do not further decrease the in vitro phenotypic susceptibility). The development of these additional RT mutations (the time of first detection, specific mutations, or number of mutations) did not have any obvious correlation with the viral RNA set point of the STI animals (Fig.…”
Section: Fig 4 Virus Levels Genotypic Drug Resistance and Cd4mentioning
confidence: 50%